Distinct lateral variations of upper mantle anisotropy beneath eastern China revealed by shear‐wave splitting. (12th June 2013) - Huang, Hui; Xu, Mingjie; Wang, Liangshu; Huang, Zhouchuan; Wang, Pan; Mi, Ning; Li, Hua; Yu, Dayong
Abstract: [1] A dense seismic array consisting of 28 temporary stations was deployed to study the crustal and upper‐mantle deformations beneath eastern China. We measured the splitting parameters in the crust and mantle by analyzing P ‐to‐ S phases converted at the Moho discontinuity (called PmS phases) and the core‐mantle boundary (i.e., core phases), respectively. The splitting parameters of core phases are retrieved at most stations while that of the PmS phases are retrieved at only a few stations. Distinct lateral variations of the fast polarization directions analyzed with the core phases are found in different tectonic blocks in eastern China. The delay times in the mantle and crust are moderately large (~1 s) and averagely smaller than 0.3 s, respectively. By the Fresnel‐zone analysis, the laterally variant lithospheric anisotropy is revealed between the two sub‐blocks (Southeast China Orogenic Belt and Yangtze Craton) of the eastern South China Block. In contrast, in the southeastern North China Craton, the anisotropy in a relatively deep layer contributes to the splitting observations. Key Points: Distinct lateral variations of upper mantle anisotropy in eastern China Variant lithospheric anisotropy in eastern South China Block Contribution from a relatively deep anisotropic layer in SE North China Craton